Algunas aves de puerto asís, comisaria del putumayo, colombia (1966)
From Puerto Asís (Corregimiento de la Comisaría del Putumayo, Colombia) very few records of birds are found in the literature, but this paper treats 100 specimens representative of 39 species and subspecies collected there from June 26 to July 1st., 1964. Formicarius analis zamorae Chapman and Empidonomus a. aurantio-atro-cristatus (Lafresnaye and D'Orbigny) are new for the Colombian ornis. The present study combines the ornithological knowledge of Amazonian Colombia, Ecuador and Perú.